Fossorial adaptations in African mole-rats (Bathyergidae) and the unique appendicular phenotype of naked mole-rats - Montoya-Sanhueza, Germán; Šaffa, Gabriel; Šumbera, Radim; Chinsamy, Anusuya; Jarvis, Jennifer U M; Bennett, Nigel C (Communications biology, 2022)
Life underground has constrained the evolution of subterranean mammals to maximize digging performance. However, the mechanisms modulating morphological change and development of fossorial adaptations in such taxa are still poorly known. We assessed the morpho-functional diversity and early postnatal development of fossorial adaptations (bone superstructures) in the appendicular system of the African mole-rats (Bathyergidae), a highly specialized subterranean rodent family. Although bathyergids can use claws or incisors for digging, all genera presented highly specialized bone superstructures associated with scratch-digging behavior. Surprisingly, Heterocephalus glaber differed substantially from other bathyergids, and from fossorial mammals by possessing a less specialized humerus, tibia and fibula. Our data suggest strong functional and developmental constraints driving the selection of limb specializations in most bathyergids, but more relaxed pressures acting on the limbs of H. glaber. A combination of historical, developmental and ecological factors in Heterocephalus are hypothesized to have played important roles in shaping its appendicular phenotype.
Keywords: Mole Rats; fyziologická adaptace; aklimatizace; Animals; Phenotype; Acclimatization; zvířata; fenotyp; mikroftalmičtí podzemní hlodavci; Adaptation, Physiological